HUBUNGAN KETERSEDIAAN ALAT KONTRASEPSI DENGAN PERILAKU PENGGUNAAN METODE KONTRASEPSI JANGKA PANJANG (MKJP) DI WILAYAH KERJA PUSKESMAS BATAKTE - Mili Arthanedi Jumetan; Arman Rifat Lette; Aysanti Yuliana Paulus (STIKes CHMK, 2023)
One of the objectives of the Family Planning (KB) program is to space pregnancies by using contraceptive methods for pregnancy prevention and family planning. The success of family planning services can be achieved through support from community members by actively participating as family planning participants or family planning acceptors.Akseptor KB adalah anggota masyarakat yang mengikuti gerakan KB dengan melaksanakan penggunaan alat kontrasepsi (BPS, 2019). This type of research is a quantitative research using descriptive analytic method with a cross sectional study design. Data analysis used univariate and bivariate analysis. Data analysis used univariate and bivariate analysis. The sample in this study was 100 people. The sampling technique in this study was random sampling, namely 100 active family planning acceptors in the villages of Lifuleo, Tesabela and Oenesu in 202. This data analysis uses the Chi-square test with an α value of 0.005. Results: age characteristics show that 51% of respondents are in the healthy age group, most of the respondents have a low level of education, namely 58%, the variable availability of alkon most of the respondents answered that it is always available, namely 60%, respondents who choose the distance to a health facility> 20 minutes namely 100% or all respondents, while according to the status of family planning participants most of the respondents were with Non-MKJP participant status, namely 63%. Conclusion: There is a significant relationship between education level and the behavior of using Long-Term Contraceptive Methods with p Value = 0.012 (<0.05) while for the variable availability of contraceptives there is no relationship with the behavior of using MKJP with p Value = 0.735 (> 0.05 ). Keywords: MKJP, Education, Availability of Contraceptives